PENERAPAN MEDEMEPODI UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN DAN PEMBAGIAN PADA SISWA KELAS 5 SD NEGERI SUMBERANGET 01 - Nur Huda, Jefri Indriansyar; Utami, Amaira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
The low participation of students in the learning process at SDN Sumberanget 01, Ledokombo District, Jember Regency, has resulted the low achievement of the 5th graders. To overcome these problems, this research was conducted by utilizing concrete stick objects (Medemepodi) as learning media to improve student learning outcomes. The subjects of this study consisted of 17 fifth grade students at SDN Sumberanget 01. This study applied the Classroom Action Research (CAR) method which consisted of two cycles. The research data was obtained from observing teacher’s and student’s activities as well as the results of student’s learning outcomes. The results showed that in the first cycle, there was an increase in the success rate of learning from 45% to 64%, while in second cycle it reached 100%. The research findings show that the demonstration method and cutting stick media (Medemepodi) by using concrete stick objects can improve the learning outcomes of fifth graders at SDN Sumberanget 01, Ledokombo District, Jember Regency.